2017
DOI: 10.1016/j.neulet.2016.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive ability in Down syndrome and its relationship to urinary neopterin, a marker of activated cellular immunity

Abstract: Urine neopterin may have potential as a biomarker for memory decline in Down syndrome, and could potentially also help to track progression of mild cognitive impairment (MCI) to Alzheimer's disease in other high risk populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The results of this study clearly confirm previous reports that significantly higher levels of hs-CRP and neopterin were observed in T2D complicated with foot ulcers [19,21]. Higher serum levels of neopterin among T2D compared with T1D patients indicates activation of cell-mediated immune response and increase in reactive oxygen species [22,23]. Previous studies showed that neopterin levels were influenced by proinflammatory and anti-inflammatory cytokines and this explains the insignificant correlation between serum neopterin and hs-CRP levels observed in this study [24].…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study clearly confirm previous reports that significantly higher levels of hs-CRP and neopterin were observed in T2D complicated with foot ulcers [19,21]. Higher serum levels of neopterin among T2D compared with T1D patients indicates activation of cell-mediated immune response and increase in reactive oxygen species [22,23]. Previous studies showed that neopterin levels were influenced by proinflammatory and anti-inflammatory cytokines and this explains the insignificant correlation between serum neopterin and hs-CRP levels observed in this study [24].…”
Section: Discussionsupporting
confidence: 90%
“…Numerous reports have described a relationship between the presence of AD in Down syndrome (DS) and the generation of epileptic seizures [ 31 , 182 , 183 , 184 , 185 , 186 , 187 , 188 ], correlating with a progressive deterioration of cognitive and motor functions. Both conditions appear in older patients with DS and up to 84% demented patients with DS develop seizures [ 8 ].…”
Section: Seizures In Ftdp-17 and Other Dementiasmentioning
confidence: 99%
“…Similarly to the findings in plasma neopterin levels described above, urine neopterin might also have a potential as a biomarker of AD in DS. In a longitudinal study involving individuals with DS it was shown that neopterin/creatinine levels correlated with cognitive performance over time [87].…”
Section: Fluid Biomarkers Of Ad In Ds (Table 2)mentioning
confidence: 99%